2008
DOI: 10.1038/sj.cdd.4402300
|View full text |Cite
|
Sign up to set email alerts
|

Blocking granule-mediated death by primary human NK cells requires both protection of mitochondria and inhibition of caspase activity

Abstract: Human GraB (hGraB) preferentially induces apoptosis via Bcl-2-regulated mitochondrial damage but can also directly cleave caspases and caspase substrates in cell-free systems. How hGraB kills cells when it is delivered by cytotoxic lymphocytes (CL) and the contribution of hGraB to CL-induced death is still not clear. We show that primary human natural killer (hNK) cells, which specifically used hGraB to induce target cell death, were able to induce apoptosis of cells whose mitochondria were protected by Bcl-2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 41 publications
2
31
0
Order By: Relevance
“…Indeed, our own previous studies suggested perforin pores formed on the plasma membrane were too small to allow diffusion of membrane impermeable dyes because when conventional concentrations of the membrane impermeable dye PI (0.5-1.5 mM) were used, PI staining was only observed in cells late in apoptosis, when significant accumulation of PI had occurred in DNA. 24,27 We recently demonstrated by cryo-EM analyses that the dimensions of the perforin pore (150-200Å) are easily large enough to accommodate the passage of granzymes (;50Å) and, by default, smaller nuclear dyes. These new structural insights led us to revisit the mechanism by which CLs use the pore-forming perforin to deliver granzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, our own previous studies suggested perforin pores formed on the plasma membrane were too small to allow diffusion of membrane impermeable dyes because when conventional concentrations of the membrane impermeable dye PI (0.5-1.5 mM) were used, PI staining was only observed in cells late in apoptosis, when significant accumulation of PI had occurred in DNA. 24,27 We recently demonstrated by cryo-EM analyses that the dimensions of the perforin pore (150-200Å) are easily large enough to accommodate the passage of granzymes (;50Å) and, by default, smaller nuclear dyes. These new structural insights led us to revisit the mechanism by which CLs use the pore-forming perforin to deliver granzymes.…”
Section: Discussionmentioning
confidence: 99%
“…The human cell line HeLa was maintained as previously described. 30 Primary mouse NK cells were isolated and purified from mouse by negative selection (Mouse NK Isolation Kit, MACS, Miltenyi Biotec GmbH, Bergisch Gladbach, Germany) as previously described, 31 and cultured in RPMI 1640 media supplemented as above with 1000 units/ml human recombinant IL-2. NKs were used for cytotoxicity assays between day 5 and 8 following isolation.…”
Section: Methodsmentioning
confidence: 99%
“…Notably, the mechanism of cell death activated by GZMB maybe dependent on the species (78) as well as on the type of cell transformation (96). In humans, it has been shown that cell cytotoxicity of cytokineactivated human NK cells is greatly reduced by inhibiting GZMB (97,98), confirming that GZMB is the main cell death inductor in CLs. To further prove that cell death induced by GZMB is important during Tc cell-mediated cancer immunotherapy we used the LCMV gp33 antigen model.…”
Section: Who Makes What During Cell Death Induced By Cls?mentioning
confidence: 99%